PRINSIP FIRST TO FILE DALAM RANGKA PERLINDUNGAN MEREK DI INDONESIA - Arista, Windi; Indriani, Santi (Faculty of Law, University of Palembang, 2024)
Brand is part of business strategy and is the image and reputation of the company, especially for manufacturers. There are no manufacturers who do not use brands as the identity of their products or services. Brands are identities that distinguish a company from other companies. Because the Trademark Law in Indonesia adheres to a constitutive system where the principle of first to principal is upheld, so that those who register first hold exclusive rights and deserve legal protection. Trademark registration provides stronger protection against trademark infringement, especially if it conflicts with similar or similar brands. Many businesses realize the importance of using brands to distinguish their goods from competitors' goods, but not everyone realizes the importance of trademark protection through registration. One of the goals of the law is to realize social justice, and with this protection, justice will be realized.